2014
DOI: 10.1371/journal.pone.0112270
|View full text |Cite
|
Sign up to set email alerts
|

Selenium Accumulation in Unicellular Green Alga Chlorella vulgaris and Its Effects on Antioxidant Enzymes and Content of Photosynthetic Pigments

Abstract: The aim of the present study was to investigate selenite effects in the unicellular green algae Chlorella vulgaris as a primary producer and the relationship with intracellular bioaccumulation. The effects of selenite were evaluated by measuring the effect of different selenite concentrations on algal growth during a 144 h exposure period. It was found that lower Se concentrations (≤75 mg L−1) positively promoted C. vulgaris growth and acted as antioxidant by inhibiting lipid peroxidation (LPO) and intracellul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
72
1
8

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(87 citation statements)
references
References 65 publications
(68 reference statements)
6
72
1
8
Order By: Relevance
“…The induction of antioxidants in response to enhanced ROS production is generally proportional to the duration and severity of the stress applied to algal cultures (Sun et al, 2014). In our study, it was observed that Se accumulation resulted in higher activities of SOD, POX, GPX and GR after 72 h ( Table 2).…”
Section: Effect Of Selenium On Isozyme Patterns Of Antioxidant Enzymessupporting
confidence: 49%
See 1 more Smart Citation
“…The induction of antioxidants in response to enhanced ROS production is generally proportional to the duration and severity of the stress applied to algal cultures (Sun et al, 2014). In our study, it was observed that Se accumulation resulted in higher activities of SOD, POX, GPX and GR after 72 h ( Table 2).…”
Section: Effect Of Selenium On Isozyme Patterns Of Antioxidant Enzymessupporting
confidence: 49%
“…Algae Ulva species and Chlorella vulgaris showed induced expression of SOD enzyme activity in response to ROS production caused by different Se compounds (Schiavon et al, 2012;Sun et al, 2014). The production of H 2 O 2 can be reduced to water by catalase, ascorbate peroxidase and peroxidase or through the ascorbate (AsA)-GSH cycle (Feng and Wei, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Also, Chlorella extracts modulated oxidative and inflammatory responses from human peripheral blood mononuclear cells stimulated by heat-killed P. acnes [19]. Sun et al (2014) proposed the use of selenium-enriched C. vulgaris cultures as means to induce bioaccumulation, producing antioxidant-rich biomass with applications in agriculture and human diet. Data showed that C. vulgaris is satisfactorily tolerant to selenium accumulation in culture [42].…”
Section: Dietary Use and Effects Of Chlorella On Healthmentioning
confidence: 99%
“…Sun et al (2014) proposed the use of selenium-enriched C. vulgaris cultures as means to induce bioaccumulation, producing antioxidant-rich biomass with applications in agriculture and human diet. Data showed that C. vulgaris is satisfactorily tolerant to selenium accumulation in culture [42].…”
Section: Dietary Use and Effects Of Chlorella On Healthmentioning
confidence: 99%
“…Yellow catfish restricted to freshwater habitats has become a favorite food fish due to its excellent meat quality; and has become an important freshwater aquaculture species due to its high commercial value (Sun, Zhong, Huang, & Yang, 2014). However, many diseases have become the restricted factor for catfish farming development.…”
Section: Introductionmentioning
confidence: 99%